Fighting Mixed-Species Microbial Biofilms With Cold Atmospheric Plasma - Rao, Yifan; Shang, Weilong; Yang, Yi; Zhou, Renjie; Rao, Xiancai (Frontiers in Microbiology, 2020)
Most biofilms in nature are formed by multiple microbial species, and such mixed-species biofilms represent the actual lifestyles of microbes, including bacteria, fungi, viruses (phages), and/or protozoa. Microorganisms cooperate and compete in mixed-species biofilms. Mixed-species biofilm formation and environmental resistance are major threats to water supply, food industry, and human health. The methods commonly used for microbial eradication, such as antibiotic or disinfectant treatments, are often ineffective for mixed-species biofilm consortia due to their physical matrix barrier and physiological interactions. For the last decade, an increasing number of investigations have been devoted to the usage of cold atmospheric plasma (CAP), which is produced by dielectric barrier discharges or plasma jets to prevent or eliminate microbial biofilms. Here, we summarized the production of CAP, the inactivation of microorganisms upon CAP treatment, and the microbial factors affecting the efficacy of CAP procedure. The applications of CAP as antibiotic alternative strategies for fighting mixed-species biofilms were also addressed.